In vitro assessment of the antimicrobial effects of pomegranate (Punica granatum L.) peel decoction on saliva samples - Solon José de Oliveira Leite; Flávia Moreira de Oliveira; Luiza Maria da Silveira Almeida; Michélia Antônia do Nascimento Gusmão; Luciana Moreira Chedier; Eveline Gomes Vasconcelos; Marcelo Silva Silvério; Priscila de Faria Pinto (Revista de Ciências Farmacêuticas Básica e Aplicada, 2014)
Several products have been developed to eliminate or reduce potential pathogenic microorganisms of the oral microbiome. The continuous use of these synthetic products can result in side effects such as vomiting, diarrhea, darkening of the teeth and the induction of microbial resistance. Pomegranate (Punica granatum) peel decoction was tested to assess its antimicrobial activity. In vitro analysis showed the decoction had antimicrobial activity against strains of Pseudomonas aeruginosa and Candida albicans, but none was detected against Enterococcus faecalis. When tested on saliva samples from children, the decoction showed great potential in reducing the load of microorganisms, the inhibition haloes produced with saliva samples being similar to those of the antimicrobial control (0.12% chlorhexidine). The pomegranate peel decoction in water could thus provide a promising source for developing solutions for use against oral diseases.